Peningkatan Keterampilan Proses Sains Melalui Kegiatan Belajar Tanaman Di Taman Kanak-Kanak Aba Air Bangis - Ranti Marliza; Delfi Eliza (IICET (Indonesian Institute for Counseling, Education and Therapy), 2019)
This study aims to determine the improvement of science process skills through plant learning activities. This type of research is classroom action research (CAR). The subject of the study was a kindergarten ABA kindergarten with a total of 15 people. This research was conducted for two months, namely in September and October. This research was conducted 2 cycles. The research data were collected by observation and documentation, the data were then processed using percentage techniques. The results of this study indicate there is an increase in children’s science process skills carried out cycle I precentace 40,0% and cycle II percentace 93,3%. so that it can be concluded that children’s science process skills can be increased in learning that is very enjoyable.